Understanding the Use of Information Technology as a Supporting Media for Student Learning at SMK Negeri 1 Lubuk Pakam - Ella Silvana Ginting; Apren Halomoan Hutasoit (Jurnal Mantik, 2021)
In the industry 4.0 revolution the current desirable data was faster, and practical to acquire. Especially among the students of the vocational high school did much to learn about theoretical understanding and with the practice of fieldwork. But in the performance of the theoretical learning process, students are no longer capable of critical thinking on a matter or a case given by their teachers. On these occasions, students go obout participating in activities to encourage and enlighten students about how to use good information technology. This service was carried out in a vocational high school (SMK) state 1 to 336 students of al the various vocational. This activity is carried out using the method teacher centered, which is to provide material exposure to sudents regarding the use of the internet. To get an information on concering students understanding in using the internet first post test and after service activities have been done pre-test for. As a result of this activity, which students unutially assume that either the articles or information they obtain over the internet are just as good for job completion needs without sorting things out first, and once this dedicated activity opens up the minds of students that the informations can open up new opportunies for them to complete their education in vocational high school state 1 Lubuk Pakam.